O dispositivo alta nos Centros de Atenção Psicossocial/CAPS : loucura, vida cotidiana e organização social - Pinheiro, Frederico Leão (2009)
The present paper proposes an analysis about the Brazilian Psychiatric Reform as a public policy and deriving from a research developed with the workers of a Psychosocial Attention Centre III (CAPS III) and the managers of the Psychosocial Attention Web (REAP) in Aracaju. This analysis is developed as an investigation of the discharge at those services, understood not as a procedure, but as a dispositive from which different elements can be articulated: users, knowledge, technical procedures, police measures, juridical decisions, laws, services edifying. This, form the background of the articulation between mental alienation and the subject of right alienation, in the ways through which this articulation develops to the relations between madness,citizenship, internment and substitutive practices. Our investigation about the discharge as a dispositive was built with some narrative constructions, as a discourse analysis inspired by Michel Foucault s method, from the perspective of some of the main dispositive operators: workers and managers. The main aspect observed were: the articulations built by the discharge as a dispositive based on two discursive grate, the Reform as a new treatment substituting internship, and the Reform as juridical insertion and users rights practice; the exercise of these discursive grades based on the workers and managers perspective; the transference of limitations and contradictions of these grades to the competence of the dispositive operators, emerged in an outstanding way, as sometimes those operators are liable for the emergent limitations and difficulties, and some other times they are restrained by their institutional role, which is to maintain the domination relations articulated by the dispositive; finally, some aspects extracted which the dispositive operators - when they were expected to act in a way to maintain certain power relations - were capable to resist, managing other power relations from the dispositive, that we call, as Agamben, dispositive profanity